Improving the supply chain in logistics (The Peerian Journal, 2024)
In the mid-1990s, when supply chain management was just beginning to develop, it was interpreted as a kind of supplement to the logistics of cargo transportation. Currently, supply chain management is considered an independent scientific discipline. One of the main concepts in logistics is the concept of flow. are formed by deliveries. Along with the development of cooperation and specialization of enterprises, supply management styles also developed. If we summarize all the variety of points of view on the relationship between logistics and supply chain management, we can draw the following conclusion: logistics is mainly focused on the local functions of the physical implementation of the flow of reformatting materials, while supply chain management is focused on the entire value chain and on the creation of links between local functions both within the enterprise and at the inter-organizational level. Supply chain management is a part of logistics, whereas logistics, in turn, is a part of supply chain management. Other elements of supply chain management are production management, strategic management, operational management, quality management, marketing, information technology, production organization, engineering sciences. The role of the network aspects of logistics and supply chain management is becoming increasingly important, as logistics solutions are highly dependent on the technology of a particular network.